Effect of morphology and impact of the electrode/electrolyte interface on the PEC response of Fe2O3 based systems – comparison of two preparation techniques. Issue 69 (19th November 2020) - Asha, Kumari; Satsangi, Vibha Rani; Shrivastav, Rohit; Kant, Rama; Dass, Sahab
Abstract : Schematic representation of comparative morphological studies conducted on Fe2 O3 based systems at different pHs. Abstract : The present study is a comparative account of Fe2 O3 based photoelectrodes prepared by two different techniques, namely spray pyrolysis and electrochemical deposition, followed by photoelectrochemical analysis at pH 13 (highly alkaline) and pH 8 (near neutral) in 0.1 M NaOH solution for solar hydrogen generation. The study also investigates the influence of morphology at the semiconductor electrode/electrolyte interface along with quantitative determination of the morphological parameters of the rough electrode surface affecting the photoelectrochemical response using power spectral density analysis. Studies revealed that the Fe2 O3 sample (E_100cy) prepared with 100 cycles of electrochemical deposition showed the highest photocurrent density of 2.37 mA cm −2 and 1.18 mA cm −2 at 1 V vs. SCE at pH 13 and 8 respectively. Power spectral density analysis exhibited that E_100cy possesses smallest surface features contributing to the PEC response with a lower cut off length scale of 17.23, upper cut off length scale of 150.45, maximum fractal dimension of 2.62 and maximum average rms roughness of 17.52 nm, offering the maximum surface area for charge transfer reactions at the electrode/electrolyte interface. The sample E_100cy exhibited the highest ABPE of 1.29% and IPCE of 37.5%.